Posture stabilization of Skid Steer Wheeled Mobile Robots - Mohammadpour, E; Naraghi, M; Gudarzi, M (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
This paper represents the posture stabilization of a Skid Steer Wheeled Mobile Robot (SSWMR). Although, in mobile robots lateral skidding of the wheels occurs when turning at high speed, wheels of a SSWMR laterally skid in every rotational maneuver even for low speeds yielded the non-skidding nonholonomic constraint to be violated. In order to compensate the effects of parameter uncertainties, an adaptive torque controller is developed based on tunable dynamic oscillator. The Globally Uniformly Ultimately Bounded (GUUB) stability of the system to an arbitrarily small neighborhood of the origin is proved. To demonstrate the performance of the proposed controller, modeling of a SSWMR was implemented through ADAMS.